A review of thermal and thermocatalytic valorization of food waste. Issue 8 (13th April 2021) - Ebikade, Elvis Osamudiamhen; Sadula, Sunitha; Gupta, Yagya; Vlachos, Dionisios G.
Abstract : A review of thermal and thermocatalytic valorization of food waste into biobased platform chemicals. A detailed summary of process level and fundamental kinetic insights are provided towards upgrading FW to useful products for a circular economy. Abstract : Food waste (FW) remains a global challenge due to the increasing demand for food production to support a growing global population and the lack of effective waste management technologies for recycling and upcycling. Unique compounds in FW – such as carbohydrates, proteins, lignin, fats, and extractives – can be repurposed to produce important biobased fuels, bulk chemicals, dietary supplements, adsorbents, and antibacterial products, among many others. We review the thermal and thermocatalytic FW valorization strategies and the fundamental pathways. We discuss the potential integration of various valorization processes, their economic viability, the technical and marketing challenges, and the need for further developments. By overcoming several technical hurdles, repurposing FW into modular plants can create exciting economic and environmental prospects.